Desafios e possibilidades do programa de Moradia Estudantil: Uma avaliação na perspectiva dos discentes beneficiários - Oliveira, Bruno César de (2022)
The present work had the purpose of elaborate an intervention proposal for the Student Rectory for Student and Community Affairs (PRAEC) of the Federal University of Lavras (UFLA), in order to implement actions that enable shared management, through a greater participation between managers and students. PRAEC aims to expand access to education, providing minimum conditions for poor students to graduate. In this context, it seeks to expand access mechanisms and support the permanence of students in a situation of socioeconomic vulnerability. Among the programs developed by PRAEC, Student Housing, the object of this study, is one of the priority actions of the National Student Assistance Plan (PNAES). To this end, we made use of critical analysis of secondary data, arranged in reports of the institution and other entities, such as the National Forum of Pro-Rectors for Community and Student Affairs (FONAPRACE). In addition, interviews were conducted with the beneficiary students of the UFLA student housing program. The analysis of the interviews used the technique of content analysis, which allowed us to gather the most relevant information from the participants. That said, we sought to answer the following question: what are the main challenges and possibilities of the UFLA student housing program? And yet, how can the Institution manage that space more democratically, considering the need to guarantee broad access to the Program, thinking not only about the material issue, but also about the issues of strengthening citizenship, autonomy and social identity of students? From the research, of a qualitative associated with quantitative, descriptive and exploratory nature, it was demonstrated that the student housing program contributes to the student's permanence, due to its multi-dimensional character, but that, however, the policies developed need to be made in a more democratic and participatory way, in order to be concerned with issues beyond the material benefits available to the poorest students. As a way of proposing an intervention in student housing, a management system was created, which aims to increase participation and improve communication between program managers and students.